HUMORAL IMMUNE RESPONSE BEFORE AND AFTER SURGICAL THERAPY IN PATIENTS WITH ODONTOGENIC INFLAMMATORY CYSTS - Stojanova, Irena; Dimitrovski, Oliver; Markovska Arsovska, Mirjana; Bajrami, Muhamet; Nikolovski, Bruno (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Odontogenic inflammatory cysts are pathological lesions that are often represented in clinical practice and they presented potential focal points with an impact on other organs and systems in the body. The aim    of this research is to compare the patients’ humoral immune response by verifying the level of immunoglobulins IgA, IgG and IgM in the serum before and one month after surgical therapy in patients with odontogenic inflammatory cysts. 44 male and female patients diagnosed with odontogenic inflammatory cysts were included in the study and divided into three groups (Group 1-patients with radicular cysts-23, Group 2-patients with residual cysts-10 and, Group 3-patients with periodontal cysts-11).  Тhe values ​​of IgA, IgM and IgG in serum werе examined before and one month after the surgical therapy in the device Cobas 6000 model c501 (Roche, Germany). In all three examined parameters of humoral immunity (IgA, IgG and IgM in serum), a significant difference was observed in the patients in addition to a decrease in their values ​​1 month after the surgical intervention compared to before the intervention. The level of IgA before and 1 month after intervention between the three groups of patients did not indicate a significant difference for a consequent p=0.2716 vs. p=0.2898. A significant difference between the three groups of patients, before and 1 month after the surgery, was also not found in terms of the IgG level for a consequent p=0.2692 vs. p=0.3614. The comparison of the three groups of patients regarding the level of IgM in serum indicated a significantly higher value of this parameter in patients with periodontal cyst compared to radicular and residual cyst before the intervention (p=0.0067) and 1 month after the intervention (p=0.0263). The levels of immunoglobulins in patients with odontogenic inflammatory cysts before surgical treatment were significantly elevated, depending on the type of the cyst. Their surgical removal generate a decrease in their level. These findings suggest that IgA, IgG and IgM may play an important role in the occurrence, development and persistence of cystic lesions. Keywords: Odontogenic inflammatory cysts, immunological analysis, humoral immune response, immunoglobulins IgA IgG and IgM.